2018
DOI: 10.2174/1871530317666171120152048
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model of the Prevalence of Delirium in Elderly Subjects Admitted to Nursing Homes

Abstract: The prevalence of delirium among elderly subjects admitted to nursing homes was 60.7%. Infections (with the exception of urinary tract infections), dementia, anticholinergic drug use, depression and urinary incontinence were predictive of the presence of delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Figure 1 illustrates the study selection process, with 29 studies 20 , 21 , 22 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 being retained for a meta‐analysis of the associations between delirium and UTI, comprising 16,618 participants, with 26 studies 20 , 21 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the study selection process, with 29 studies 20 , 21 , 22 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 being retained for a meta‐analysis of the associations between delirium and UTI, comprising 16,618 participants, with 26 studies 20 , 21 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , ...…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the main meta‐analysis of 29 studies 20 , 21 , 22 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 expressing associations between delirium and UTI in older adults. 95% CI, 95% confidence interval …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From our review, we identified 28 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] articles with relevant data regarding the prevalence of delirium, and eight articles [ 11 , 26 , 39 , 40 , 41 , 42 , 43 , 44 ] described the incidence of delirium. Total population mean age ranged from 76.2 years to 88.5 years, and 46.8% to 90.8% of the participants in the studies were female.…”
Section: Review Resultsmentioning
confidence: 99%
“…Infections were characterized by higher odds of delirium onset [ 28 ]. Furthermore, urinary and respiratory infections were mentioned as important precipitating risk factors [ 25 , 39 ].…”
Section: Review Resultsmentioning
confidence: 99%